2013
DOI: 10.1128/aem.02184-12
|View full text |Cite
|
Sign up to set email alerts
|

Functional γ-Aminobutyrate Shunt in Listeria monocytogenes: Role in Acid Tolerance and Succinate Biosynthesis

Abstract: Listeria monocytogenes, the causative agent of human listeriosis, is known for its ability to withstand severe environmental stresses. The glutamate decarboxylase (GAD) system is one of the principal systems utilized by the bacterium to cope with acid stress, a reaction that produces ␥-aminobutyrate (GABA) from glutamate. Recently, we have shown that GABA can accumulate intracellularly under acidic conditions, even under conditions where no extracellular glutamate-GABA exchange is detectable. The GABA shunt, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…GabT is one of the key enzymes of the glutamate decarboxylase (GAD) system that catalyzes glutamate to the ␥-aminobutyrate (GABA). The GABA shunt pathway has been suggested to provide an alternative source of succinate in bacteria and a way to generate energy from glutamate without production of ammonia (16,17). The in vitro and macrophage assays demonstrated that while delayed killing was observed for an M. smegmatis clone overexpressing the GabT protein during treatment with anti-TB drugs, significant reduction in time was seen in an M. tuberculosis GabT-deficient mutant.…”
Section: Tuberculosis Metabolic "Escape" Pathwaysmentioning
confidence: 95%
“…GabT is one of the key enzymes of the glutamate decarboxylase (GAD) system that catalyzes glutamate to the ␥-aminobutyrate (GABA). The GABA shunt pathway has been suggested to provide an alternative source of succinate in bacteria and a way to generate energy from glutamate without production of ammonia (16,17). The in vitro and macrophage assays demonstrated that while delayed killing was observed for an M. smegmatis clone overexpressing the GabT protein during treatment with anti-TB drugs, significant reduction in time was seen in an M. tuberculosis GabT-deficient mutant.…”
Section: Tuberculosis Metabolic "Escape" Pathwaysmentioning
confidence: 95%
“…Arginine decarboxylase enzyme has one substrate (L-arginine) and two products, CO2 and agmatine, which has been showed to be a competitive inhibitor in E. coli (Blethen et al, 1968). GAD converts glutamate in γ -aminobutyrate (GABA) and is well described in L. monocytogenes for instance (Cotter et al, 2001; Gandhi and Chikindas, 2007; Karatzas et al, 2010, 2012; Feehily et al, 2013). …”
Section: Ph Homeostasismentioning
confidence: 99%
“…Similarly deletion of gabT and gabD that encode for the GABA shunt that catabolize intracellular GABA pools produced by the intracellular GAD system (Feehily et al . ), resulted in resistance in sterile water but not in wastewater. It has been suggested that the GAD system, together with the GABA shunt feed in the TCA cycle, are affecting the levels of succinate and oxoglutarate that have antioxidant properties and, thus can confer resistance to oxidant species (Ramond et al .…”
Section: Resultsmentioning
confidence: 99%